2020
DOI: 10.46405/ejms.v2i2.111
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Implications of COVID-19 in Kenya

Abstract: Dear Editor, As the COVID-19 pandemic continues to spread rapidly worldwide, it is certainly having an immense effect on the mental wellbeing of people thereby increasing the number of people with elevated levels of stress, depression, or anxiety.1 Developing countries will undoubtedly have serious mental health implications due to the poor or almost non-existent mental health services. In Kenya, mental health is still somewhat neglected mainly because only 0.05% of the Governments’s health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Despite all the efforts to contain the COVID-19 pandemic in low-resource countries, psychological distress among healthcare providers remains notably high in Sub-Saharan countries. 17 A more inclusive evidence-based understanding of HCWs’ psychological burden during the COVID-19 is vital for providing psychological support, improving mental health services in low resource countries. 18 The HCWs on the frontline who have been directly involved in the diagnosis, treatment, and care of patients with COVID-19 may be at significant risk of developing mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the efforts to contain the COVID-19 pandemic in low-resource countries, psychological distress among healthcare providers remains notably high in Sub-Saharan countries. 17 A more inclusive evidence-based understanding of HCWs’ psychological burden during the COVID-19 is vital for providing psychological support, improving mental health services in low resource countries. 18 The HCWs on the frontline who have been directly involved in the diagnosis, treatment, and care of patients with COVID-19 may be at significant risk of developing mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Kenya is, therefore, looking at the second pandemic of mental health complications associated with COVID-19. 22 The front-line health employees, including doctors, nurses, ambulance drivers, case identifiers (Contact tracers), are all targets of discrimination during this pandemic. The research found that the medical staff of Sudan showed that they were suffering from anxiety and depression during the COVID-19 outburst.…”
Section: Sub-saharan Africamentioning
confidence: 99%
“…The rising levels of mental health and related issues such as depression, suicide and self-harm are not given much attention yet "it is undeniable that the fear of uncertain future and stigma of Covid-19 is fuelling mental health crisis in Kenya" (Ochillo & Elsie, 2020). The need to prioritize mental health, especially at the community level during this pandemic cannot thus be overemphasized.…”
Section: Mental Health Situation In Kenya During Covid-19 Pandemicmentioning
confidence: 99%